2020
DOI: 10.1002/slct.202002907
|View full text |Cite
|
Sign up to set email alerts
|

On the Electronic Origins of the Different Behaviors of S+ and S2+/2+ in Methane Activation

Abstract: The thermal gas‐phase reactions of S+, S2+ and S22+ with methane have been explored by using quadrupole‐ion trap (Q‐IT) mass spectrometry complemented by quantum chemical calculations. In contrast to the reactiveness of the S+/CH4 and S22+/CH4 couples as identified by experiment and computation, respectively, the S2+/CH4 couple is inert at ambient temperature. Interestingly, the hydrogen‐atom transfer (HAT) prevails for S+/CH4 and proton‐coupled electron transfer (PCET) for S2+/CH4, while both PCET and hydride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…These authors assumed that H 3 CS + is formed, which is impossible because S + is a quadruplet while H 3 CS + is a triplet, and it would be impossible energetically for the spin conservation rules. Indeed, Yu et al (2020) found that the corrected product seen by Smith et al (1981) is H 2 CSH + (singlet) and not H 3 CS + , as corroborated by our calculations that found the channel producing H 2 CSH + to be exothermic. Please note that to reintroduce the reaction with the correct reaction channel (H 2 CSH + ) would require revising all the reactions involving H 3 CS + and H 2 CSH + , which is beyond the scope of the present work.…”
Section: Comparison With the Umist Databasesupporting
confidence: 84%
“…These authors assumed that H 3 CS + is formed, which is impossible because S + is a quadruplet while H 3 CS + is a triplet, and it would be impossible energetically for the spin conservation rules. Indeed, Yu et al (2020) found that the corrected product seen by Smith et al (1981) is H 2 CSH + (singlet) and not H 3 CS + , as corroborated by our calculations that found the channel producing H 2 CSH + to be exothermic. Please note that to reintroduce the reaction with the correct reaction channel (H 2 CSH + ) would require revising all the reactions involving H 3 CS + and H 2 CSH + , which is beyond the scope of the present work.…”
Section: Comparison With the Umist Databasesupporting
confidence: 84%
“…The experiments were performed in a self-designed, quadrupole-ion trap mass spectrometer (see Figure 1), as described elsewhere. 41,42 The Osmium-carbide cluster ions OsC 2 + or Iridium-carbide cluster ions IrC controlled by pulsed valves. The ions are sent into the quadrupole mass filter through a 5 mm diameter hole of a skimmer, and then the ions are guided into the ion trap (also the reaction cell) through a 5 mm diameter hole of the electric shielding plate and react with CH 4 or 13 CH 4 (reaction time is 10 ms), which is introduced into the reaction cell via a leak valve.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed in a self-designed, quadrupole-ion trap mass spectrometer (see Figure ), as described elsewhere. , The Osmium-carbide cluster ions OsC 2 + or Iridium-carbide cluster ions IrC 2 + are generated by pulsed laser (532 nm, Nd:YAG) ablation of a rotating and translating solid target (compressed Osmium and graphite powder (1:2; volume ratio) or Iridium and graphite powder (1:2.5; volume ratio)) in the presence of Ar carrier gas (99.999%) with a stationary backing pressure of 0.5 MPa. The carrier gas is controlled by pulsed valves.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%